STUDENTS’ SATISFACTION IN ENGLISH LEARNING THROUGH WAYGROUND: A QUANTITATIVE STUDY IN INDONESIAN JUNIOR HIGH SCHOOL - Maharani Maharani; Yessicka Noviasmy; Zulfah Fakhruddin; Nurul Hasanah (Esteem Journal of English Education Study Programme, 2026)
This study investigates students’ satisfaction with English language learning facilitated through the Wayground application in an Indonesian Islamic junior high school context. Specifically, it examines students’ levels of satisfaction across four key dimensions: perceived usefulness, perceived ease of use, system quality, and overall learning experience among eighth-grade learners. Employing a descriptive quantitative approach, the study involved 33 participants selected through a total sampling technique. Data were gathered using a 20-item questionnaire developed based on the Technology Acceptance Model (TAM) and the Information Systems Success Model, and subsequently analyzed using descriptive statistical methods. The results indicate that students report consistently high levels of satisfaction across all measured dimensions. The Wayground application is viewed as beneficial, user-friendly, and effective in enhancing students’ engagement, motivation, and overall learning experiences in English language instruction. The findings offer valuable insights for English teachers, instructional designers, and educational policymakers seeking to integrate gamified digital learning platforms into EFL classrooms, particularly at the junior high school level. Furthermore, this study enriches the existing body of literature by providing empirical evidence on learners’ satisfaction with the Wayground application within the context of Indonesian Islamic junior high schools, an educational setting that remains underrepresented in previous research.